MODERNIZATION OF UKRAINIAN EDUCATION UNDER GLOBAL CHALLENGES AND LOCAL CULTURAL EMBEDDEDNESS - Yakymchuk , Oksana (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2026)
Contemporary Ukrainian education develops within the tension between global transformations and local cultural embeddedness, which raises the problem of combining openness to global trends with the preservation of national cultural specificity. The aim of the article is to investigate the main aspects of modernization of Ukrainian education under global challenges and local cultural embeddedness. The tasks are to substantiate the conceptual foundations and strategic orientations of modernization through the combination of global trends with the national cultural context without loss of cultural identity, and to examine the role of local cultural embeddedness in preserving national specificity. Research methods. The study is based on the dialectical method of G. Hegel, the hermeneutic approach of H.-G. Gadamer (“fusion of horizons”), and the conceptual framework of nonlinear dynamics (I. Prigogine, I. Stengers) used as an analytical tool. Research results. It is shown that modernization occurs through the dialectical interaction of global and local dimensions rather than linear adaptation. Global standardization and digitalization often conflict with local cultural meanings, while education develops through reinterpretation of external influences within its own cultural context. Instability, interpreted through bifurcation, is considered not only as a threat but also as a condition for the emergence of new educational forms, intensified by wartime transformations. Discussion. The study demonstrates that neither uncritical adoption of global models nor isolation within national tradition is productive. The most effective perspective is a synthetic model based on dialogical interaction of global and local elements. Conclusions. The study shows that modernization of Ukrainian education should be understood as a nonlinear process shaped by the tension between global transformations and local cultural embeddedness. In this context, instability does not merely indicate crisis but functions as a condition for the emergence of new educational configurations. The analysis demonstrates that the development of the educational system depends on its ability to reinterpret global influences within its own cultural horizon rather than reproduce them mechanically. Such reinterpretation enables the formation of a flexible and adaptive model capable of responding to contemporary challenges, including wartime transformations and uncertainty.